Design rules for light-emitting electrochemical cells delivering bright luminance at 27.5 percent external quantum efficiency - Tang, Shi; Sandström, Andreas; Lundberg, Petter; Lanz, Thomas; Larsen, Christian; Reenen, Stephan van; Kemerink, Martijn; Edman, Ludvig (Nature Communications, 2017)
Cost-efficient light-emitting electrochemical cells can deliver unique functions, but suffer because strong brightness has only been obtained at modest efficiency. Tang et al. report on rationally designed devices that are both bright and efficient, thus representing a major step towards commercialization.